Aspirin therapy reduces the ability of platelets to promote colon and pancreatic cancer cell proliferation: Implications for the oncoprotein c-MYC - Mitrugno, Annachiara (Am J Physiol Cell Physiol, 2017)
Aspirin, an anti-inflammatory and antithrombotic drug, has become the focus of intense research as a potential anticancer agent owing to its ability to reduce tumor proliferation in vitro and to prevent tumorigenesis in patients. Studies have found an anticancer effect of aspirin when used in low, antiplatelet doses. However, the mechanisms through which low-dose aspirin works are poorly understood. In this study, we aimed to determine the effect of aspirin on the cross talk between platelets and cancer cells. For our study, we used two colon cancer cell lines isolated from the same donor but characterized by different metastatic potential, SW480 (nonmetastatic) and SW620 (metastatic) cancer cells, and a pancreatic cancer cell line, PANC-1 (nonmetastatic). We found that SW480 and PANC-1 cancer cell proliferation was potentiated by human platelets in a manner dependent on the upregulation and activation of the oncoprotein c-MYC. The ability of platelets to upregulate c-MYC and cancer cell proliferation was reversed by an antiplatelet concentration of aspirin. In conclusion, we show for the first time that inhibition of platelets by aspirin can affect their ability to induce cancer cell proliferation through the modulation of the c-MYC oncoprotein.